ANALISIS PENDAPATAN PEDAGANG KAKI LIMA SELAMA MASA PEMBUKAAN ALUN-ALUN AIMAS KABUPATEN SORONG - Rokhimah; Andi Hasrun; Karfin; Agilistya Rahayu (KALIANDA HALOK GAGAS, 2023)
In this study the aim was to analyze whether income from street vendors had an effect on before and after the opening of Aimas Square. For this study, we used secondary data sourced from scientific journals and primary data sourced directly from interviews conducted in the field. which the analysis was carried out using qualitative analysis. The results of this study indicate that there are differences in income for street vendors before and after the opening of Aimas Square. So that there were several traders who moved locations when the Square was closed